Projetos pedagógicos do curso de graduação em biomedicina : análise das conquistas e desafios em relação às diretrizes curriculares nacionais - Pellegrino, Cristiane Zappulla (2015)
The National Curriculum Guidelines – DCN of the Biomedicine undergraduate course have been enacted on February 18, 2003 and are aligned to a new society requirement for the training of health professionals in the country. These demands point to the need for a new profile, as well as strategies and methodologies aimed at forming a critical, reflective and contextualized society in the Unified System of Health - SUS. Under this challenge, it must be the need to expand the production of studies, to identify the potential and the challenges in the design and development of educational proposals, which can translate the curriculum guidelines in articulated and integrated content to SUS’s practices, aiming a new professional training. This research proposed the construction of an evaluation matrix whose goal is aimed at promoting self-assessment by stakeholders in biomedicine training. This matrix was formed by two axes (I) Biomedicine Curriculum and Axis (II) Biomedical Professional Profile, according to the DCN constituent elements of Biomedicine Undergraduate Programs. For a better discussion about the constructed matrix adequacy, this was applied to a set Pedagogical Projects Course - PPC biomedicine undergraduate. The sample consisted of Federal Institutions Courses in the southeast of Brazil who obtained Preliminary Course Concept (CPC) 4 and 5 in the National Survey of Student Performance (NSSP), in 2013. PPC Analysis revealed that the category with the closest approach in relation to DCN was Curricular Content, and the category with greater distance was the Health and Biomedicine education. The application of the matrix showed power of this evaluative tool to identify strengths and challenges in the PPC self-assessment in the light of the National Curriculum Guidelines.